2021
DOI: 10.3390/su13052794
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Social Responsibility in the Adoption of Business Practices

Abstract: Corporate social responsibility (CSR) policies are evidenced by adopting socially relevant business practices for people, communities, companies, and related institutions. Based on this conception, the present work determines the incidence of ethics and CSR on practices regarding diversity, environment, and community of Chilean companies. The method, applied to a sample of 3179 Chilean companies, was descriptive and correlational. Results demonstrate an incipient level of standardization in the adoption of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Many studies claim that companies are realizing that generating funds requires an ethical foundation (41,42). Hence, ethical CSR is a powerful tool of differentiation and offers various benefits to companies, such as advocacy, purchase intentions, consumer loyalty, and building a positive corporate image (43)(44)(45). Based on the above discussion, we can propose our hypothesis as follows.…”
Section: Ethical Csrmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies claim that companies are realizing that generating funds requires an ethical foundation (41,42). Hence, ethical CSR is a powerful tool of differentiation and offers various benefits to companies, such as advocacy, purchase intentions, consumer loyalty, and building a positive corporate image (43)(44)(45). Based on the above discussion, we can propose our hypothesis as follows.…”
Section: Ethical Csrmentioning
confidence: 95%
“…Ethical responsibility is identified by minimization of risk and internal control system that can lead to the offering of products that are beneficial for consumers. Related works of literature have asserted the impact of unethical CSR and ethical CSR on the corporate image and found that ethical CSR enhances corporate image significantly (29,43,48). Philanthropic CSR corresponds to improving the quality of life for society as a whole by donating the resources of a company, facilities, and time to the community of an employee for free.…”
Section: Csr Dimensions and Corporate Imagementioning
confidence: 99%
“…The integrated communication strategies of electric cooperatives contribute to building trust and credibility with stakeholders. Authors such as Dopazo-Fraguío [68]; Orozco-Toro and Ferré-Pavia [69]; Falcón Pérez [24]; and Arenas-Torres, Bustamante-Ubilla, and Campos-Troncoso [70] have analyzed, from a multidisciplinary perspective, different relational processes to manage dialogue, commitment, and co-orientation between organizations and stakeholders through CSR, from the perspective of stakeholder theory, circular economy theory, and network theory [30,71,72]. Following the implementation of standardized reporting monitoring models, CSR strategies should respond to the corporative goals defined in the different stages of the Value Curve.…”
Section: Csr Management With Stakeholders In Electric Cooperativesmentioning
confidence: 99%
“…The consubstantial level, which is governed by the principles of cooperative and sustainable governance, has a direct impact on the contextual level through the cooperative fund for social actions in the local community. Campos-Troncoso [70] have analyzed, from a multidisciplinary perspective, different relational processes to manage dialogue, commitment, and co-orientation between organizations and stakeholders through CSR, from the perspective of stakeholder theory, circular economy theory, and network theory [30,71,72]. Following the implementation of standardized reporting monitoring models, CSR strategies should respond to the corporative goals defined in the different stages of the Value Curve.…”
Section: Csr Management With Stakeholders In Electric Cooperativesmentioning
confidence: 99%
“…With these two foci, CSR embodies ethics of justice and care [28], helps employees find meaningfulness through work [29], and guides organizations to concrete actions as a responsible corporate citizen [30]. Some take a step toward CSR by making donations and engaging in philanthropic activities; others work on embedding the spirit in their culture; some even endeavor to link business strategies with CSR, and vice versa, as a method to pursue both their competitive advantage and community contributions [31].…”
Section: Socially Responsible Managementmentioning
confidence: 99%